مكافحة الجرائم ذات الصلة بتمويل الإرهاب - زويوش, ريم; مباركي, دليلة (University of Eloued جامعة الوادي, 2021)
لقد تزايد الاهتمام الدولي بمكافحة تمويل الإرهاب وذلك لتقييد نشاط المنظمات الإرهابية والحيلولة دون تحقيقها لأهدافها، ومدها بالإعانات التي تحتاجها. وتهدف عمليات تمويل الإرهاب إلى دعم هذا الأخير، باعتبارها صورة من صور الجرائم الإرهابية، وتكمن خطورتها في اقترانها ببعض الجرائم الخطيرة، الأمر الذي جعلها محور اهتمام المجتمع الدولي، نظرا لاستفحالها واكتساحها الساحة الدولية بعد أحداث 11 سبتمبر 2001 في الولايات المتحدة الأمريكية. وتهدف هذه الدراسة إلى بيان مفهوم تمويل الإرهاب، ومصادره، والجرائم المتعلقة به وطرق مكافحتها. International attention has increased to combat the financing of terrorism, to limit the activities of terrorist organizations and to prevent them from achieving their objectives, and to expand them with the subsidies they need. The terrorist financing operations are aimed at supporting the latter as a form of terrorist crime. The danger lies in the association of some serious crimes, which has become the focus of the international community because of its spread and spread in the international arena after the events of September 11, 2001 in the United States of America. The purpose of this study is to explain the concept of financing terrorism, its sources, related crimes and methods of combating it.
مجلد12، عدد1
Keywords: تمويل، إرهاب، جريمة، أموال، تخريب; Financing, terrorisme, crime, money, sabotage